Подробно решить уравнение​

0 голосов
17 просмотров

Подробно решить уравнение​


image

Алгебра (35 баллов) | 17 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Ответ: х=3.

Объяснение:

\frac{x-2}{x^{2}-x } +\frac{1}{x^{2}+x } =\frac{2}{x^{2} -1} \\\frac{x-2}{x*(x-1)}+\frac{1}{x*(x+1)}=\frac{2}{(x-1)(x+1)}

ОДЗ: x≠0    x+1≠0    x≠-1     x-1≠0     x≠1    ⇒   x₁,₂≠±1    x₃≠0.

(x+1)*(x-2)+(x-1)*1=2*x\\x^{2} -x-2+x-1=2x\\x^{2} -2x-3=0\\D=16;\sqrt{D}=4

x₁=3 ∈ОДЗ       х₂=-1 ∉ОДЗ.

(251k баллов)